(untitled) (Research, Society and Development, 2020)
Systemic Arterial Hypertension (SAH) can generate complications such as stroke, myocardial infarction, kidney disease, arteriosclerosis, loss of vision, erectile dysfunction and cognitive dysfunction. Among people who know they suffer from hypertension, 50% use medication and of those only 45% have their blood pressure kept under control. SAH is a multifactorial clinical condition characterized by elevated and sustained blood pressure levels (BP, where systolic BP ≥ 140 mmHg and diastolic BP ≥ 90 mmHg). Faced with sparse investigative studies on the causes of SAH in individuals, the dictates of the pharmaceutical industry and the use of in vitro or inconclusive clinical studies, this paper presents the state of the art about the treatment of SAH based on a multifaceted view, including aspects about the physiology of SAH, food and PANC as alternatives for the prevention and control of SAH, as well as an approach on the importance of scientific rigor in the manufacture of medicines.